Reversible Thrombocytopenia of Functional Platelets after Nose-Horned Viper Envenomation is Induced by a Snaclec - Dobaja Borak, Mojca; Leonardi, Adrijana; Požek, Kity; Reberšek, Katarina; Podgornik, Helena; Pirnat, Aljaž; Trampuš Bakija, Alenka; Kranjc Brezar, Simona; Trobec, Tomaž; Žužek, Monika C.; Frangež, Robert; Brvar, Miran; Križaj, Igor (Thrombosis and Haemostasis, 2024)
Profound and transient thrombocytopenia of functional platelets without bleeding was observed in patients envenomed by Vipera a. ammodytes (Vaa). This condition was rapidly reversed by administration of F(ab)2 fragments of immunoglobulin G targeting the whole venom, leaving platelets fully functional. To investigate the potential role of snake venom C-type lectin-like proteins (snaclecs) in this process, Vaa-snaclecs were isolated from the crude venom using different liquid chromatographies. The purity of the isolated proteins was confirmed by Edman sequencing and mass spectrometry. The antithrombotic effect was investigated by platelet agglutination and aggregation assays and blood coagulation tests. Using flow cytometry, the platelet activation and binding of Vaa-snaclecs to various platelet receptors was analyzed. Antithrombotic efficacy was tested in vivo using a mouse model of vascular injury. Two Vaa-snaclecs were purified from the venom. One of them, Vaa-snaclec-3/2, inhibited ristocetin-induced platelet agglutination. It is a covalent heterodimer of Vaa-snaclec-3 (α-subunit) and Vaa-snaclec-2 (β-subunit). Our results suggest that Vaa-snaclec-3/2 induces platelet agglutination and consequently thrombocytopenia by binding to the platelet receptor glycoprotein Ib. Essentially, no platelet activation was observed in this process. In vivo, Vaa-snaclec-3/2 was able to protect the mouse from ferric chloride-induced carotid artery thrombosis, revealing its applicative potential in interventional angiology and cardiology.
Keywords: snake venom; reversible thrombocytopenia; snaclecs; arterial occlusion; mice; interventional cardiology; antithrombotic